Do Religious Children Care More and Provide More Care for Older Parents? A Study of Filial Norms and Behaviors across Five Nations - Oded Stark (Journal of Comparative Family Studies, 2010)
We propose an explanation for the provision of attention and care to aged parents; we suggest a reason why the presence of young children could support rather than inhibit the provision of this care; and we provide an explanation as to why daughters are more often observed to provide attention and care to parents than sons.
Keywords: A14; D10; I30; J13; J14; 330; Intergenerational transfers; Provision of attention and care to aged parents; The demonstration effect; The presence of young children supports the provision of care to parents; Inculcating values in children; Daughters' provision of attention and care to parents